Lithium ion battery

The lithium-ion battery design addresses safety issues by optimizing the puncture force and thickness ratios of separator and electrode components, reducing short circuits and thermal runaway, and ensuring stable electrical performance.

CN119208751APending Publication Date: 2024-12-27ZHUHAI COSMX BATTERY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411386253.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Lithium-ion batteries face safety issues due to short circuits between positive and negative electrodes during mechanical abuse, leading to thermal runaway and potential hazards.

Method used

A lithium-ion battery design that includes specific ratios for the puncture force and thickness of the separator, positive and negative electrode current collectors, and their respective active layers, reducing short circuit points and heat generation, while maintaining low-temperature performance and cycle stability.

Benefits of technology

The design enhances safety by minimizing thermal runaway risk and improving mechanical abuse test pass rates, while maintaining good electrical performance and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208751A_ABST
    Figure CN119208751A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery preparation, and particularly relates to a lithium ion battery. The lithium ion battery comprises a positive pole piece, a negative pole piece and a diaphragm arranged between the positive pole piece and the negative pole piece, the positive pole piece comprises a positive current collector and a positive active layer positioned on at least one side surface of the positive current collector; the negative pole piece comprises a negative current collector and a negative active layer positioned on at least one side surface of the negative current collector; the separator includes a base film; and the puncture force A of the diaphragm, the thickness B of the base film, the puncture force C of the positive current collector, the thickness D of the positive current collector, the puncture force E of the negative current collector and the thickness F of the negative current collector meet a relational expression 1. When the diaphragm puncture force, the base film thickness, the positive electrode current collector puncture force and thickness, and the negative electrode current collector puncture force and thickness in the battery meet a certain proportion, the contact between the positive electrode and the negative electrode during mechanical abuse can be reduced, the generation of short circuit points can be reduced, the heat production can be reduced, the thermal runaway occurrence probability can be reduced, and the safety performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery preparation, and in particular relates to a lithium ion battery. Background Art

[0002] Lithium-ion batteries have high volumetric energy, mass energy and cycle performance. With the development of portable electronic devices, electric vehicles, aerospace and other fields, higher demands are placed on lithium-ion batteries. High energy density and high rate performance are the development trend of lithium-ion batteries. Batteries need to take into account more stringent performance indicators, which means higher requirements are placed on their safety performance.

[0003] Existing lithium-ion batteries are composed of a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrodes. During mechanical abuse tests (such as needle puncture and heavy object impact), a short circuit will occur between the positive and negative electrodes, and the temperature of the short circuit point will rise sharply, triggering the internal material reaction to release heat. As the reaction continues to release heat, it will further trigger material reactions at other locations, leading to thermal runaway and causing safety issues. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects in the prior art that when the battery is mechanically abused, a short circuit occurs between the positive and negative electrodes, the temperature at the short circuit point rises sharply, triggering internal material reactions to continuously release heat, causing thermal runaway, and causing safety problems, thereby providing a lithium-ion battery.

[0005] To this end, the present invention provides the following technical solutions.

[0006] The present invention provides a lithium ion battery, the lithium ion battery comprising a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer located on at least one side surface of the positive electrode current collector; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector; the separator comprises a base film; the puncture force A of the separator, the thickness B of the base film, the puncture force C of the positive electrode current collector, the thickness D of the positive electrode current collector, the puncture force E of the negative electrode current collector and the thickness F of the negative electrode current collector satisfy the relationship 1:

[0007]

[0008] Among them, A is 1N-8N; B is 3μm-16μm; C is 1N-10N; D is 5μm-20μm; E is 1N-10N; and F is 3μm-20μm.

[0009] The technical solution of the present invention has the following advantages:

[0010] 1. The battery provided by the present invention comprises a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet comprises a positive current collector and a positive active layer located on at least one side of the positive current collector; the negative electrode sheet comprises a negative current collector and a negative active layer located on at least one side of the negative current collector; the separator comprises at least a base film; the puncture force A of the separator, the thickness B of the base film, the puncture force C of the positive current collector, the thickness D of the positive current collector, the puncture force E of the negative current collector and the thickness F of the negative current collector satisfy the relational formula 1. When the puncture force of the separator, the thickness of the base film, the puncture force and thickness of the positive current collector, and the puncture force and thickness of the negative current collector in the battery meet a certain ratio, the contact between the current collector and the active material during mechanical abuse can be reduced, the generation of short circuit points can be reduced, and the heat generation can be reduced, the probability of thermal runaway can be reduced, and the passing rate of the mechanical abuse test can be improved. Furthermore, the separator puncture force, base film thickness, positive electrode current collector puncture force and thickness, negative electrode current collector puncture force and thickness satisfying equation 1 can also better balance the low temperature performance of the battery, and charge and discharge under low temperature conditions (such as 0-10°C) with good cycle performance, capacity retention rate and service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0012] Figure 1 It is a schematic diagram of the deformation amount produced by the puncture force of the diaphragm when testing the present invention. DETAILED DESCRIPTION

[0013] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0014] In the description of the present invention, it should be noted that the terms "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0015] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0016] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0017] The present invention provides a lithium-ion battery, which can reduce the generation of short-circuit points, reduce the probability of thermal runaway, improve the passing rate of mechanical abuse tests, and improve the safety performance of the battery when subjected to mechanical abuse; the lithium-ion battery still has good electrical properties such as cycle performance and capacity retention rate during charging and discharging at low temperatures, and has a long service life. The lithium-ion battery can take into account both safety performance and low-temperature electrical performance. The technical solution adopted by the present invention is as follows.

[0018] In a first aspect, the present invention provides a lithium ion battery, the lithium ion battery comprising a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet comprises a positive electrode collector and a positive electrode active layer located on at least one side surface of the positive electrode collector; the negative electrode sheet comprises a negative electrode collector and a negative electrode active layer located on at least one side surface of the negative electrode collector; the separator comprises at least a base film; the puncture force A of the separator, the thickness B of the base film, the puncture force C of the positive electrode collector, the thickness D of the positive electrode collector, the puncture force E of the negative electrode collector and the thickness F of the negative electrode collector satisfy the relationship 1:

[0019]

[0020] Among them, the puncture force A of the diaphragm is 1N-8N; the thickness B of the base film is 3μm-16μm; the puncture force C of the positive electrode collector is 1N-10N; the thickness D of the positive electrode collector is 5μm-20μm; the puncture force E of the negative electrode collector is 1N-10N; the thickness F of the negative electrode collector is 3μm-20μm.

[0021] Optionally, the puncture force C of the positive electrode current collector is 1N-2.5N; the puncture force E of the negative electrode current collector is 1N-2.5N.

[0022] It is understandable to those skilled in the art that when a battery is subjected to a mechanical abuse test, a short circuit is easily generated between the positive and negative electrodes, and the temperature of the short circuit point rises sharply, triggering the internal material reaction to release heat. As the reaction release heat continues, it further triggers the reaction of materials at other locations, causing thermal runaway and potential safety hazards. In order to solve the above problems, the applicant has found that when the diaphragm puncture force, base film thickness, positive electrode current collector puncture force and thickness, and negative electrode current collector puncture force and thickness meet a certain ratio, the contact between the current collector and the active material during mechanical abuse can be reduced, the generation of short circuit points can be reduced, and heat generation can be reduced, the probability of thermal runaway can be reduced, and the pass rate of the mechanical abuse test can be improved; in particular, the contact between the positive electrode current collector and the negative electrode active material can be reduced. Furthermore, the diaphragm puncture force, base film thickness, positive electrode current collector puncture force and thickness, and negative electrode current collector puncture force and thickness meet the relationship 1, which can also better balance the low temperature performance of the battery, charge and discharge under low temperature conditions (such as 0-10°C), and have good cycle performance, capacity retention rate and service life.

[0023] The applicant found that the puncture force A of the separator is 1N-8N; the thickness B of the base film is 3μm-16μm; the puncture force C of the positive current collector is 1N-10N; the thickness D of the positive current collector is 5μm-20μm; the puncture force E of the negative current collector is 1N-10N; the thickness F of the negative current collector is 3-20μm. Controlling the above parameter ranges and satisfying equation 1 can reduce the occurrence of thermal runaway and short circuit.

[0024] As an example, A is 1N, 2N, 3N, 4N, 5N, 6N, 7N, 8N or within the range of any two of the above values; B is 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm or within the range of any two of the above values; C is 1N, 2N, 3N, 4N, 5N, 6N, 7N, 8N, 9N, 10N or within the range of any two of the above values; D is 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm , 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or in the range formed by any two of the above values; the E is 1N, 2N, 3N, 4N, 5N, 6N, 7N, 8N, 9N, 10N or in the range formed by any two of the above values; the F is 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or in the range formed by any two of the above values.

[0025] It should be noted that the puncture force of the diaphragm, positive current collector or negative current collector of the present invention refers to the maximum force applied to the needle during the penetration of the diaphragm or current collector. The puncture force of the diaphragm and the puncture force of the current collector are tested and obtained according to methods known in the art. Here is one example of using a universal tensile testing machine to test the puncture force. It includes: taking a sample with a length × width ≥ 80mm × 80mm and mounting it on a fixture, setting the puncture speed, the needle moves downward, and the puncture force is obtained through the data of the testing machine. The maximum force applied to the needle during the penetration of the sample is the puncture force. In an optional embodiment, the deformation G generated when testing the diaphragm puncture force and the thickness H of the positive electrode sheet satisfy the relationship 2;

[0026] G>H relation 2

[0027] Wherein, L1 is 1.5mm-4.5mm; H is 50μm-150μm;

[0028] Preferably, H is 60 μm-110 μm.

[0029] In an optional embodiment, the deformation G generated when testing the diaphragm puncture force and the thickness I of the negative electrode sheet satisfy the relationship 3:

[0030] G>I relation 3

[0031] Wherein, L1 is 1.5mm-4.5mm; I is 50μm-180μm;

[0032] Preferably, the I is 50 μm-100 μm.

[0033] It can be understood that the deformation amount and the thickness of the positive and negative current collectors generated when testing the puncture force of the diaphragm of the present invention satisfy the relationship 2 and / or the relationship 3, which can further reduce the contact between the current collector and the active material, thereby reducing the generation of short circuit points, further reducing the probability of thermal runaway, and improving the pass rate of the battery mechanical abuse test. As an example, the L1 is 1.5μm, 1.8μm, 2.1μm, 2.4μm, 2.7μm, 3μm, 3.3μm, 3.6μm, 3.9μm, 4.2μm, 4.5μm or within the range of any two of the above values. The H is 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm or within the range of any two of the above values. The I is 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, or within a range formed by any two of the above values. It can also be understood that the thickness H of the positive electrode sheet is the overall thickness of the positive electrode sheet; the thickness I of the negative electrode sheet is the overall thickness of the negative electrode sheet.

[0034] It should be noted that the calculation method of the deformation generated by the puncture force of the diaphragm is as follows: during the puncture process, the displacement of the needle from the time the needle just touches the diaphragm to the time the diaphragm is punctured is recorded as L1, and the distance from the point where the needle just touches the diaphragm to the edge of the fixture is recorded as R. According to the Pythagorean theorem, L2 is calculated, that is, Deformation G = L2-R, the piercing process and calculation diagram are shown in Figure 1 .

[0035] In an optional embodiment, a first coating and a positive active material layer are provided on at least one surface of the positive current collector; the first coating is provided between the positive current collector and the positive active material layer, and the first coating includes a non-conductive organic polymer; the non-conductive organic polymer can reduce the conductivity of the positive electrode sheet, increase the surface resistance, and make the short-circuit current generated during short circuit smaller, generate less heat, and facilitate passing the safety performance test. It is understandable that the non-conductive organic polymer comes from the binder in the coating, and the binder is selected from a non-conductive organic polymer.

[0036] Preferably, the non-conductive organic polymer is polymer particles.

[0037] In an optional embodiment, the surface resistance of the first coating is 1 mΩ-1000 mΩ;

[0038] In an optional embodiment, the surface resistance of the first coating layer is 1 mΩ-100 mΩ.

[0039] In an optional embodiment, the ionic conductivity J of the separator and the surface resistance K of the first coating satisfy the relationship 4:

[0040]

[0041] Wherein, the J is 0.1-2mS / cm; the K is 1mΩ-100mΩ;

[0042] Preferably, the ionic conductivity J of the diaphragm and the surface resistance K of the first coating satisfy the relationship 5:

[0043]

[0044] The applicant has found that increasing the surface resistance of the first coating increases the impedance of the positive electrode sheet, making the short-circuit current generated during short circuit smaller and generating less heat, which is conducive to passing the safety performance test, but the high-rate performance is lost. Therefore, the present invention can make up for the defect of poor conductivity caused by the first coating by making the ionic conductivity of the diaphragm meet 0.1-2mS / cm, and take into account both electrical performance and safety performance on the basis of ensuring the electrical performance of the battery. As an example, the J is 0.1mS / cm, 0.3mS / cm, 0.5mS / cm, 0.7mS / cm, 0.9mS / cm, 1.1mS / cm, 1.3mS / cm, 1.5mS / cm, 1.7mS / cm, 0.9mS / cm, 2mS / cm or within the range of any two of the above values. The K is 1 mΩ, 10 mΩ, 20 mΩ, 30 mΩ, 40 mΩ, 50 mΩ, 60 mΩ, 70 mΩ, 80 mΩ, 90 mΩ, 100 mΩ or in a range formed by any two of the above values. It should be noted that the ionic conductivity of the diaphragm is obtained by testing according to conventional methods in the art.

[0045] In an optional embodiment, the first coating contains a non-conductive organic polymer, which can increase the surface resistance and impedance, so that the short-circuit current generated during a short circuit is smaller and the heat generated is less, which is conducive to passing the safety performance test.

[0046] In an optional embodiment, the thickness M of the first coating layer, the thickness N of the separator and the thickness F of the negative electrode current collector satisfy equation 6:

[0047]

[0048] Wherein, the M is 0.1 μm-5 μm; the N is 3 μm-22 μm;

[0049] Preferably, the M is 2 μm-4 μm.

[0050] The applicant has found that by designing the thickness of the negative electrode current collector, the thickness of the diaphragm, and the thickness of the first coating in the positive electrode sheet to meet specific requirements, the pass rate of the battery mechanical abuse test can be further improved. When the negative electrode current collector is thicker, it is necessary to match a thicker diaphragm or a thicker first coating to reduce the short-circuit points generated during the mechanical abuse test. The thickness of the negative electrode current collector, the thickness of the diaphragm, and the thickness of the first coating are designed to meet the relationship 6, which can reduce the generation of short-circuit points and further improve the pass rate of the battery mechanical abuse test. As an example, the M is 0.1μm, 0.4μm, 0.7μm, 1.0μm, 1.2μm, 1.5μm, 1.8μm, 2.1μm, 2.4μm, 2.7μm, 3μm, 3.3μm, 3.6μm, 3.9μm, 4.2μm, 4.5μm, 5μm or within the range of any two of the above values. The N is 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm or within a range formed by any two of the above values. It is understood that the first coating thickness of the present invention is 0.1 μm-5 μm, which can enable the battery to have both safety performance and energy density.

[0051] It should be noted that the first coating layer can be disposed on one or both sides of the positive electrode current collector; the first coating layer is a one-layer or multi-layer structure, and when it is a multi-layer structure, the composition of each coating layer can be the same or different. It is understood that the thickness of the first coating layer refers to the thickness of the coating layer on the same side of the positive electrode current collector. As an example, the first coating layer is a single-layer structure, a two-layer structure, a three-layer structure, etc.; when the first coating layer is a multi-layer structure, its preparation method is a common method in the art, such as forming a multi-layer structure by multiple coatings.

[0052] In an optional embodiment, the components of the first coating include an inorganic filler, a binder and a conductive agent; the inorganic filler is coated with a conductive layer, and the mass ratio of the inorganic filler coated with the conductive layer, the binder and the conductive agent is (60-98): (2-40): (0-5); it should be noted that the conductive agent ratio of 0 refers to the technical solution that the components of the first coating do not contain a conductive agent. It can be understood that the inorganic filler has high mechanical strength, stability and heat resistance. In the case of mechanical abuse of the battery (such as needle puncture, extrusion), the inorganic filler can well protect the positive electrode collector, making it not easy to be exposed, reducing the contact between the positive electrode collector and the negative electrode active material, reducing the probability of short circuit, and improving the safety performance of the battery. The inorganic filler is coated with a conductive layer on the outside, which helps the battery to obtain excellent safety performance and cycle performance.

[0053] In an optional embodiment, the inorganic filler is selected from at least one of aluminum oxide, magnesium oxide, titanium oxide, zinc oxide, silicon oxide, boehmite, cobalt oxide, iron phosphate, lithium iron phosphate, lithium nickel cobalt manganese oxide, and lithium iron manganese phosphate. The resistivity of the inorganic filler coated with a conductive layer is 1Ω·cm-100Ω·cm, and the resistivity of the inorganic filler is obtained by testing according to a method known in the art. As an example, the resistivity of the inorganic filler coated with a conductive layer is 1Ω·cm, 3Ω·cm, 5Ω·cm, 7Ω·cm, 9Ω·cm, 10Ω·cm, or within the range of any two of the above values. The average particle size of the inorganic filler coated with a conductive layer is 0.05μm-5μm, preferably 100nm-600nm. As an example, the average particle size of the inorganic filler is 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm or in the range of any two of the above values.

[0054] For those skilled in the art, the conductive agent is a common raw material in the art, for example, including one or more of conductive carbon black (SP), acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, metal powder and carbon fiber. The binder is a common raw material in the art, for example, the binder includes an aqueous binder and / or an oil-based binder. The aqueous binder includes one or more of polyacrylic acid (PAA), polyacrylate, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylonitrile (PAN). The oil-based binder includes one or more of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), polyolefins (such as copolymers or homopolymers such as ethylene and propylene), fluorinated rubber, polyimide (PI) and perfluorosulfonic acid ionomer (Nafion).

[0055] In an optional embodiment, the material of the conductive layer includes at least one of ATO, FTO, ITO and carbon material; wherein ATO is tin dioxide doped with antimony, FTO is tin dioxide doped with fluorine, and ITO is indium oxide doped with tin; the doping amount of antimony in ATO is ≤30%, the doping amount of fluorine in FTO is ≤10%, and the doping amount of tin in ITO is ≤30%. It can be understood that the above conductive layer materials have a good coating effect on inorganic fillers, forming a conductive layer on the outer surface of the inorganic filler, reducing the heat propagation speed and improving the battery safety performance.

[0056] In an optional embodiment, based on the total mass of the inorganic filler coated with the conductive layer, the mass content of the conductive layer is 2wt%-40wt%, preferably 10wt%-30wt%, so that the battery has both safety performance and conductivity. As an example, the mass content of the conductive coating layer in the inorganic filler is 2wt%, 6wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or in the range of any two of the above values.

[0057] In an optional embodiment, the surface resistance of the first coating is 1mΩ-1000mΩ, preferably 1mΩ-100mΩ. As an example, the surface resistance of the first coating is 1mΩ, 5mΩ, 10mΩ, 15mΩ, 20mΩ, 30mΩ, 40mΩ, 50mΩ, 60mΩ, 70mΩ, 80mΩ, 90mΩ, 100mΩ, 200mΩ, 300mΩ, 400mΩ, 500mΩ, 600mΩ, 700mΩ, 800mΩ, 900mΩ, 1000mΩ or in the range of any two of the above values. It should be noted that the surface resistance of the first coating is obtained by testing according to a method known in the art, and a test method is listed here: using a bulk phase resistor to test the surface resistance of the coating.

[0058] In an optional embodiment, the surface density of the first coating is 0.1 mg / cm 2 -1.5mg / cm 2 , preferably 0.5 mg / cm 2 -1.2mg / cm 2 As an example, the surface density of the first coating is 0.1 mg / cm 2 , 0.3mg / cm 2 , 0.6mg / cm 2 , 0.9mg / cm 2 , 1.2mg / cm 2 , 1.5mg / cm 2 Or within the range formed by any two of the above values. It is understandable that the surface density of the first coating layer will affect the thickness of the first coating layer. The surface density of the first coating layer is 0.1 mg / cm 2 -1.5mg / cm 2 The thickness of the first coating layer may be 0.5 μm to 5 μm. It is understood that the surface density is the mass per unit area.

[0059] In an optional embodiment, the peeling force between the first coating and the positive current collector is 20N / m-1000N / m, preferably 100N / m-500N / m. As an example, the peeling force between the first coating and the positive current collector is 20N / m, 50N / m, 80N / m, 110N / m, 140N / m, 170N / m, 200N / m, 230N / m, 260N / m, 290N / m, 320N / m, 350N / m, 380N / m, 410N / m, 440N / m, 470N / m, 500N / m, 600N / m, 700N / m, 800N / m, 900N / m, 1000N / m or within the range of any two of the above values. It should be noted that the peeling force is obtained by testing according to a method known in the art. For example, a positive electrode current collector coated with the first coating having a length of 100 mm and a width of 15 mm is cut as a sample to be tested; the positive electrode current collector is fixed on the upper and lower fixtures of a universal tensile machine; the sample is peeled off at 180°, the test speed is 100 mm / min, and the test displacement distance is 80 mm. The peeling force is obtained by converting the parameters measured by the tensile machine.

[0060] In an optional embodiment, the tensile strength of the diaphragm in the TD direction is 1200-7000 kgf / cm 2 The tensile strength of the diaphragm in the MD direction is 1200-7000kgf / cm 2 and / or,

[0061] The elongation at break of the separator in the TD direction is greater than 30%, and the elongation at break of the separator in the MD direction is greater than 30%; and / or,

[0062] The puncture strength of the diaphragm is >120 gf.

[0063] As an example, the tensile strength of the separator in the TD direction is 1200 kgf / cm 2 、1500kgf / cm 2 、2000kgf / cm 2 、2500kgf / cm 2 、3000kgf / cm 2 、3500kgf / cm 2 、4000kgf / cm 2 、4500kgf / cm 2 、5000kgf / cm 2 、5500kgf / cm 2 、6000kgf / cm 2 、6500kgf / cm 2 、7000kgf / cm 2Or within the range of any two of the above values. The tensile strength of the diaphragm in the MD direction is 1200kgf / cm 2 、1500kgf / cm 2 、2000kgf / cm 2 、2500kgf / cm 2 、3000kgf / cm 2 、3500kgf / cm 2 、4000kgf / cm 2 、4500kgf / cm 2 、5000kgf / cm 2 、5500kgf / cm 2 、6000kgf / cm 2 、6500kgf / cm 2 、7000kgf / cm 2 Or within the range formed by any two of the above values. The elongation at break of the diaphragm in the TD direction is 31%, 35%, 40%, 45%, 50%, 200%, or within the range formed by any two of the above values. The elongation at break of the diaphragm in the MD direction is 31%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, 100%, 130%, 170%, 200%, or within the range formed by any two of the above values. The puncture strength of the diaphragm is 125gf, 130gf, 135gf, 140gf, 145gf, 150gf, 200gf, 300gf, 400gf, 500gf, 600gf, or within the range formed by any two of the above values.

[0064] In an optional embodiment, the thermal shrinkage of the diaphragm in the TD direction (105°C 1h) is less than 10%, and the thermal shrinkage in the MD direction (105°C 1h) is less than 10%; the friction coefficient is 0.2-0.7; the film rupture temperature is greater than 150°C; the closed cell temperature is less than 147°C; the porosity is 38%-68%; and the air permeability is 80-400s / 100cc.

[0065] It should be noted that the elongation at break, tensile strength, thermal shrinkage, puncture strength, friction coefficient, film breaking temperature, closed-cell temperature, porosity, air permeability, etc. of the diaphragm are tested and obtained according to methods known in the art. The puncture strength and puncture force have the same meaning, 1N puncture force is approximately 102gf puncture strength, and the same test method is used to obtain these two data.

[0066] The tensile strength of the diaphragm is defined as the maximum stress value required for failure under tensile stress, in kgf / cm 2. Elongation at break is defined as the ratio of the increase in the distance between gauge lengths to the initial gauge length when the material breaks under a certain tensile force, in %. Elongation at break and tensile strength are measured in accordance with the provisions of GB / T1040.3-2006, using a specimen with a width of (15±0.1) mm, an initial distance between the clamps of the tensile testing machine of (100±5) mm, and a test speed of (250±10) mm / min. The elongation at break and tensile strength of the diaphragm are measured by a tensile testing machine.

[0067] Thermal shrinkage: First, the diaphragm sample to be cut is flatly clamped in A4 paper, and placed in a punching mold to punch into a size of 100×100mm; secondly, the length is measured using a 2.5D microscope, and the horizontal and vertical lengths are recorded; then the diaphragm sample clamped in A4 paper is placed in an oven and baked at 105℃ for 1h. After cooling for 10min after baking, the diaphragm is immediately measured with a microscope and the thermal shrinkage rate is calculated; the calculation formula for the diaphragm shrinkage rate is:

[0068] Transverse direction (TD) = (width before baking - width after baking) / width before baking × 100%

[0069] Machine direction (MD) = (length before baking - length after baking) / length before baking × 100%.

[0070] Porosity: First, stack the diaphragm into 6 layers, flatten it, and press it tightly to remove the air in the diaphragm. Cut the stacked diaphragm according to the cutting board, and measure the cut samples to obtain the sample area S. Then measure the thickness of the sample 10 times and calculate the average value B. Use an electronic balance to measure the weight of the diaphragm 3 times and obtain the average value M. Calculate the porosity of the diaphragm according to the following formula:

[0071] Porosity C (%) = [(density of diaphragm raw material×S×B-M) ÷ (density of diaphragm raw material×S×B)]×100%.

[0072] Air permeability: Use a membrane air permeability tester to test the membrane air permeability.

[0073] Friction coefficient: A dynamic friction coefficient tester is used, and the test method is as follows: cut a current collector with a length of 100 mm and a width of 80 mm, place it on a smooth plane, take a 75mm×75mm diaphragm, fix it on a 65mm×65mm slider, and move the slider forward at a constant speed of 100mm / min. The friction force is measured and then the dynamic friction coefficient is obtained.

[0074] Membrane rupture temperature and closed-cell temperature: First, you need to build a battery for testing, which will be used for subsequent heating and resistance measurement; secondly, place the test battery in a temperature-controlled environment, gradually heating from 30°C to 200°C. During the heating process, you need to record the temperature of the test battery and its corresponding resistance value every 5 seconds. Finally, draw the temperature-resistance curve of the test battery based on the recorded data. By calculating the resistance change at intervals of 5 seconds, when the resistance value increases by more than 50Ω for the first time or the resistance value decreases by more than 50Ω for the first time, the closed-cell temperature and membrane rupture temperature are determined respectively. That is, when the resistance value increases by more than 50Ω for the first time, it is recorded as the closed-cell temperature, and when the resistance value decreases by more than 50Ω for the first time, it is recorded as the membrane rupture temperature.

[0075] In an optional embodiment, the base film has a thickness of 3-16 μm; and / or a porosity of 25%-50%; and / or a permeability of 50s / 100cc-250s / 100cc; and / or a pore size distribution of 20-90nm. As an example, the thickness of the base film is 3μm, 6μm, 9μm, 12μm, 16μm or in the range of any two of the above values; the porosity is 25%, 30%, 35%, 40%, 45%, 50% or in the range of any two of the above values; the permeability is 50s / 100cc, 80s / 100cc, 110s / 100cc, 140s / 100cc, 170s / 100cc, 200s / 100cc, 250s / 100cc or in the range of any two of the above values; the pore size distribution is 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or in the range of any two of the above values.

[0076] It should be noted that the material of the base film is selected from raw materials known in the art and is not limited thereto; as an example, the material of the base film includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polyphenylene sulfide, polyimide, polystyrene, polytetrafluoroethylene, polymethyl methacrylate, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, cellulose, etc.

[0077] In an optional embodiment, the diaphragm further includes a coating, which is located on at least one surface of the base film; the coating includes at least one layer structure of a rubber layer and a ceramic layer; the ceramic layer is at least arranged on one surface of the base film, and the thickness of the ceramic layer is 0.3μm-4μm. It should be noted that the thickness of the ceramic layer refers to the total thickness on one side of the diaphragm. As an example, the thickness of the ceramic layer is 0.3μm, 0.9μm, 1.5μm, 2.1μm, 2.7μm, 3.3μm, 4.0μm or within the range of any two of the above values. It is understandable that the ceramic layer can be a one-layer or multi-layer structure. When the ceramic layer is a multi-layer structure, the components of each layer are the same or different, and multiple coating methods are used.

[0078] In an optional embodiment, the peeling force between the ceramic layer and the base film is higher than 10 N / m. As an example, the peeling force between the ceramic coating and the substrate layer is 10.5 N / m, 11 N / m, 13 N / m, 15 N / m, 17 N / m, 19 N / m, 21 N / m, 23 N / m, 25 N / m, 30 N / m, 45 N / m, 70 N / m, or within a range formed by any two of the above values.

[0079] In an optional embodiment, the components of the ceramic layer include inorganic particles and a binder, and optionally, the mass ratio of the inorganic particles to the binder is (40-95):(5-60); the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silicon dioxide, tin oxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, cerium dioxide, zirconium titanate, barium titanate and magnesium fluoride; the binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene and polyhexafluoropropylene.

[0080] In an optional embodiment, the adhesive layer is disposed on at least one surface of the base film and / or the ceramic coating. As a preferred embodiment, the adhesive layer is disposed on the outer surface of the ceramic layer.

[0081] In an optional embodiment, the thickness of the adhesive layer is 0.3 μm-6 μm; as an example, the thickness of the adhesive layer is 0.3 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, or within a range formed by any two of the above values. It should be noted that the thickness of the adhesive layer is the thickness on the same side of the base film layer, that is, the single-sided thickness.

[0082] In an optional embodiment, the peeling force between the adhesive layer and the base film is higher than 10 N / m; the peeling force between the adhesive layer and the substrate layer is 11 N / m, 13 N / m, 15 N / m, 17 N / m, 19 N / m, 21 N / m, 23 N / m, 25 N / m, or within a range formed by any two of the above values. It is understood that the peeling strength between the adhesive layer and the base film is higher than the peeling strength between the ceramic layer and the base film.

[0083] In an optional embodiment, the coating layer contains a polymer, which is granular and / or non-granular, and the particle size is the same or different; the polymer is a common polymer in the art; for example, the polymer includes a copolymer or homopolymer formed by at least one monomer of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, butyl acrylate, ethylhexyl acrylate, styrene, α-methylstyrene, vinyltoluene, ethylene, vinyl acetate, acrylonitrile, vinylidene fluoride, hexafluoropropylene, and chlorophthalic anhydride; the polymer can also be at least one of polyetherimide, polyamideimide, polyimide, and a copolymer of vinylidene fluoride and hexafluoropropylene.

[0084] In an optional embodiment, the bonding strength between the separator and the positive electrode plate is 0-80 N / m; the bonding strength cannot be 0. As an example, the bonding strength between the separator and the positive electrode plate is 1 N / m, 3 N / m, 8 N / m, 10 N / m, 20 N / m, 30 N / m, 40 N / m, 50 N / m, 60 N / m, 70 N / m, 80 N / m, or within a range formed by any two of the above values.

[0085] The bonding strength between the separator and the negative electrode plate is 0-80 N / m; the bonding strength cannot be 0. As an example, the bonding strength between the separator and the negative electrode plate is 1 N / m, 3 N / m, 8 N / m, 10 N / m, 20 N / m, 30 N / m, 40 N / m, 50 N / m, 60 N / m, 70 N / m, 80 N / m, or within a range formed by any two of the above values.

[0086] In an optional embodiment, the tensile strength of the negative electrode current collector in the TD direction is not less than 400MPa; preferably, the tensile strength of the negative electrode current collector in the MD direction is not less than 400MPa; and / or, the elongation of the negative electrode current collector in the TD direction is not less than 2%; preferably, the elongation of the negative electrode current collector in the MD direction is not less than 2%. As an example, the tensile strength of the negative electrode current collector in the TD direction is 400MPa, 500MPa, 600MPa, 700MPa, 800MPa, 900MPa or in the range of any two of the above values, preferably 700MPa. The tensile strength of the negative electrode current collector in the MD direction is 400MPa, 500MPa, 600MPa, 700MPa, 800MPa, 900MPa or in the range of any two of the above values, preferably 700MPa. As an example, the elongation of the negative electrode current collector in the TD direction is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or in the range of any two of the above values, preferably not less than 5%. The elongation of the negative electrode current collector in the MD direction is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or in the range of any two of the above values, preferably not less than 5%.

[0087] In an optional embodiment, the surface density of the negative electrode current collector is not less than 26 mg / m 2 As an example, the surface density of the negative electrode current collector is 26 mg / m 2 , 27mg / m 2 , 28mg / m 2 , 29mg / m 2 , 30mg / m 2 , 31mg / m 2 , 32mg / m 2 , 33mg / m 2 , 34mg / m 2 Or within the range of any two of the above values. It is understandable that the surface density of the negative electrode current collector will affect the thickness of the negative electrode current collector. The surface density of the negative electrode current collector is not less than 26 mg / m 2 , so that it can have a more suitable thickness. It is well known to those skilled in the art that the negative electrode current collector is copper foil, nickel foil, titanium foil, iron-nickel alloy foil, etc.

[0088] In an optional embodiment, the negative electrode plate includes a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector; the negative active material layer is a one-layer or multi-layer structure, and when the negative active material layer is a multi-layer structure, the composition of each layer may be the same or different. It is understood that the composition of the negative active material layer includes active materials, and the active materials are common raw materials in the art, such as at least one of carbon-based materials, silicon-based materials, tin-based materials, and titanium-based materials; specifically, at least one of artificial graphite, natural graphite, soft carbon, hard carbon, elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon nitrogen composites, silicon alloys, elemental tin, tin oxide compounds, tin alloys, elemental titanium, titanium oxide compounds, and titanium alloys. It is also understood that the composition of the negative active material layer may also include additives, such as conductive agents, binders, and the like. Conductive agents and binders are of known types in the art and are not specifically limited thereto. For example, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, carbon fibers and Ketjen black; the binder includes at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber and polyvinylidene fluoride.

[0089] In an optional embodiment, at least one surface of the negative electrode current collector is also provided with a second coating; as a preferred embodiment, the second coating is provided between the negative electrode current collector and the negative electrode active material layer, and the second coating helps to remove and embed lithium ions and improve the transmission of lithium ions during the charge and discharge process; the thickness of the second coating is 0.01μm-3μm; the second coating is a carbon coating, which improves the bonding between the active material and the current collector, ensures good contact, and reduces or prevents problems such as detachment. As an example, the thickness of the second coating is 0.01μm, 0.1μm, 0.5μm, 1.0μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm or is within the range of any two of the above values. It is understood that the thickness of the second coating is the thickness of the coating on the same side of the current collector. It should be noted that the second coating is a one-layer or multi-layer structure. It can also be understood that the components of the second coating include carbon materials and may also include components such as binders.

[0090] As a preferred embodiment, the negative electrode plate includes a negative electrode current collector and a second coating layer arranged on both sides of the negative electrode current collector, and the negative electrode active material layer is arranged on the surface of the second coating layer.

[0091] In an optional embodiment, the negative electrode current collector contains a doping element; the doping element includes at least one of Cr, Fe, Mg, Mn, Sb, Si, Sn, Ti and Zn. The negative electrode current collector containing the doping element is helpful to refine the grains and further improve the tensile strength and elongation.

[0092] In an optional embodiment, the content of the doping element in the negative electrode current collector is not higher than 1000 ppm.

[0093] In an optional embodiment, the negative electrode current collector is provided with a groove; the depth of the groove is not higher than the thickness of the negative electrode current collector; the diameter of the groove is not higher than 100 μm; the spacing between adjacent grooves is 0.05 mm-0.5 mm. The negative electrode current collector is provided with a groove to increase the electrolyte wettability of the negative electrode, prevent lithium deposition on the surface of the negative electrode, prevent lithium dendrites from piercing the diaphragm, further prevent the positive and negative electrode plates from directly contacting each other to cause a short circuit in the battery, improve the safety performance of the battery under high temperature conditions, and improve high temperature cycle performance.

[0094] In an optional embodiment, the tensile strength of the positive electrode current collector in the TD direction is not less than 200MPa; preferably, the tensile strength of the positive electrode current collector in the MD direction is not less than 200MPa; and / or, the elongation of the positive electrode current collector in the TD direction is not less than 2%; preferably, the elongation of the positive electrode current collector in the MD direction is not less than 2%. As an example, the tensile strength of the positive electrode current collector in the TD direction is 200MPa, 300MPa, 400MPa, 500MPa, 600MPa, 700MPa, 800MPa, 900MPa or in the range of any two of the above values. The tensile strength of the positive electrode current collector in the MD direction is 200MPa, 300MPa, 400MPa, 500MPa, 600MPa, 700MPa, 800MPa, 900MPa or in the range of any two of the above values. As an example, the elongation of the positive electrode current collector in the TD direction is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or within the range of any two of the above values. The elongation of the positive electrode current collector in the MD direction is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or within the range of any two of the above values.

[0095] In an optional embodiment, the surface density of the positive electrode current collector is not less than 10 mg / m 2 As an example, the surface density of the positive electrode current collector is 26 mg / m 2 , 27mg / m 2 , 28mg / m 2 , 29mg / m 2 , 30mg / m2 , 31mg / m 2 , 32mg / m 2 , 33mg / m 2 , 34mg / m 2 Or within the range of any two of the above values. It is understandable that the surface density of the positive electrode current collector will affect the thickness of the positive electrode current collector. The surface density of the positive electrode current collector is not less than 26 mg / m 2 , so that it can have a more suitable thickness. It is well known to those skilled in the art that the positive electrode current collector is aluminum foil or the like.

[0096] It should be noted that the surface density is obtained by testing according to a method known in the art. For example, a punching machine with a punching diameter of 12 mm / 16 mm is used to punch out a small disc of the current collector without any material attached, and the disc is weighed and the weight m is recorded; the area of ​​the punched disc is calculated according to the diameter of the small disc, and the disc area s is recorded; the current collector surface density is obtained using m / s. It can also be understood that the surface density of the current collector is the unit area mass of the current collector.

[0097] In an optional embodiment, the positive electrode current collector contains doping elements; the doping elements include at least one of Cr, Fe, Mg, Mn, Sb, Si, Sn, Ti and Zn; the content of doping elements in the positive electrode current collector is not higher than 1000ppm. It is understandable that the composition of the positive electrode active material layer includes positive electrode active materials, which are common raw materials in the art, such as at least one or more of lithium nickel oxide, lithium titanate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide. The composition of the positive electrode active material layer also includes auxiliary agents, which include binders, conductive agents, etc. The binder includes at least one of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber and styrene-acrylic rubber; the conductive agent includes at least one of conductive carbon black, carbon nanotubes, conductive graphite and graphene; the active material and auxiliary agent are selected in a common ratio in the art, and the present invention does not limit this.

[0098] In an optional embodiment, the battery further comprises an electrolyte; the electrolyte comprises an electrolyte salt and a solvent; the electrolyte further comprises an additive. It is understandable that the electrolyte is a common raw material for preparing batteries in the art.

[0099] In an optional embodiment, the electrolyte salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0100] In an optional embodiment, the solvent includes at least one of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).

[0101] In an optional embodiment, the additive includes a film-forming additive on the surface of the negative electrode, a film-forming additive on the surface of the positive electrode, and a film-forming additive on the surface of the positive and negative electrode current collectors; and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc. The additive may be a nitrile compound such as a dinitrile compound, a trinitrile compound, a cyclic carbonate having a carbon-carbon double bond, a fluorinated chain carbonate, a fluorinated cyclic carbonate, or a sulfur-oxygen double bond compound, and the following compounds are listed here:

[0102] The dinitrile compounds include, but are not limited to, succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, 1,10-dicyanodecane, 1,12-dicyanododecane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylvaleronitrile, 2,2,4,4-tetramethyl Glutaronitrile, 1,5-dicyanopentane, 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether, diethylene glycol di(2-cyanoethyl) ether ) ether, triethylene glycol di(2-cyanoethyl) ether, tetraethylene glycol di(2-cyanoethyl) ether, 3,6,9,12,15,18-hexaoxaicosanoic acid dinitrile, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl) ether, 1,4-dicyano-2-butane 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene or 1,6-dicyano-2-methyl-5-methyl-3-hexene.

[0103] The trinitrile compounds include, but are not limited to, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane, or 1,2,5-tris(cyanoethoxy)pentane.

[0104] Cyclic carbonates having a carbon-carbon double bond include, but are not limited to, vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, fluorovinylene carbonate, trifluoromethyl vinylene carbonate; vinyl ethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, 1-n-propyl-2-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1,1-divinylethylene carbonate, 1,2-divinylethylene carbonate; 1,1-dimethyl-2-methyleneethylene carbonate, 1,1-diethyl-2-methyleneethylene carbonate.

[0105] The fluorinated chain carbonates include, but are not limited to, fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate or bis(trifluoroethyl) carbonate.

[0106] Fluorinated cyclic carbonates include, but are not limited to, fluoroethylene carbonate, 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4,5-difluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4,4-difluoro-5-methylethylene carbonate, 4-(fluoromethyl)-ethylene carbonate, 4-(difluoromethyl)-ethylene carbonate, 4-(trifluoromethyl)-ethylene carbonate, 4-(fluoromethyl)-4-fluoroethylene carbonate, 4-(fluoromethyl)-5-fluoroethylene carbonate, 4-fluoro-4,5-dimethylethylene carbonate, 4,5-difluoro-4,5-dimethylethylene carbonate, 4,4-difluoro-5,5-dimethylethylene carbonate.

[0107] The compounds containing sulfur-oxygen double bonds include, but are not limited to, cyclic sulfates, chain sulfates, chain sulfonates, cyclic sulfonates, chain sulfites, cyclic sulfites, chain sulfites, chain sulfones, cyclic sulfones, and the like.

[0108] In an optional embodiment, the electrolyte comprises a lithium salt, an organic solvent, an additive A and an additive B, wherein the additive A is a dinitrile compound containing a carbon-carbon double bond, and the additive B is a silane phosphate compound and / or a silane borate compound. The content of the dinitrile compound containing a carbon-carbon double bond is 0.5 to 10% of the total weight of the electrolyte. The content of the additive B is 0.5 to 10% of the total weight of the electrolyte, and further preferably, the total content of the silane phosphate compound and the silane borate compound is 1 to 5% of the total weight of the electrolyte.

[0109] In an optional embodiment, the electrolyte includes an organic solvent, a lithium salt and an additive. The additive includes a phosphoric acid cyclic anhydride compound and a dinitrile compound containing an unsaturated bond; the mass percentage of the phosphoric acid cyclic anhydride compound in the non-aqueous electrolyte is 0.1% to 3%; the mass percentage of the dinitrile compound containing an unsaturated bond in the non-aqueous electrolyte is 0.1% to 4%.

[0110] In an optional embodiment, the electrolyte includes a lithium salt, an organic solvent, and an additive. The additive includes a cyclic sulfate, a fluorocarbon surfactant, and a dinitrile compound containing a carbon-carbon double bond. The content of the cyclic sulfate is 1% to 5% of the total weight of the electrolyte; the content of the fluorocarbon surfactant is 0.05% to 0.1% of the total weight of the electrolyte; the content of the dinitrile compound containing a carbon-carbon double bond is 1% to 5% of the total weight of the electrolyte.

[0111] In an optional embodiment, the electrolyte includes a lithium salt, an organic solvent, and an additive. The organic solvent includes a carboxylate compound; the additive includes a dinitrile compound containing a carbon-carbon double bond and a silyl sulfate compound. The content of the dinitrile compound containing a carbon-carbon double bond is 0.5% to 10% of the total weight of the electrolyte; the content of the silyl sulfate compound is 0.5% to 10% of the total weight of the electrolyte; the volume of the carboxylate compound is 5% to 50% of the total volume of the organic solvent, preferably 10% to 40%, and more preferably 20% to 35%.

[0112] It should be noted that one or more auxiliary agents can be selected during use, depending on the usage requirements.

[0113] Example 1

[0114] This embodiment provides a battery, including:

[0115] (1) Positive electrode

[0116] TiO2 and PVDF were mixed in a mass ratio of 95:5, NMP was added, and the mixture was stirred to obtain a first coating slurry with a solid content of 40%, which was then coated on both surfaces of an aluminum foil and dried to obtain a first coating; wherein, the TiO2 was coated with ATO, the content of ATO in the ATO-coated TiO2 was 10wt%, and the average particle size was 0.4μm; wherein, the puncture force C and thickness D of the aluminum foil are shown in Table 1.

[0117] Lithium cobalt oxide, conductive carbon black, and polyvinylidene fluoride (PVDF) were added to a stirring tank at a mass ratio of 97.2:1.5:1.3, and then NMP solution was added and stirred thoroughly to form a uniform positive electrode active slurry; the slurry was coated on the surface of the first coating, dried, and rolled to obtain a positive electrode sheet coated with the first coating and the active material layer. The single-side thickness M of the first coating in the positive electrode sheet after rolling, the coating surface resistance K, and the positive electrode sheet thickness H are shown in Table 1.

[0118] (2) Negative electrode

[0119] Graphite, Super-P, and sodium carboxymethyl cellulose were added to a stirring tank at a mass ratio of 97:1.5:1.5, and deionized water was added. After sufficient stirring, a uniform negative electrode active slurry was obtained. The negative electrode active slurry was coated on the two surfaces of the negative electrode current collector (copper foil), and then dried to remove moisture. Rolling, slitting, and sheeting were performed in sequence to obtain the desired negative electrode sheet. The thickness F of the negative electrode current collector, the puncture force E, and the thickness I of the negative electrode sheet are shown in Table 1.

[0120] (3) Electrolyte

[0121] In a glove box filled with argon and with qualified water and oxygen content, ethylene carbonate, propylene carbonate, propyl propionate and ethyl propionate were mixed evenly in a mass ratio of 1:2:5:2, and then fully dried lithium hexafluorophosphate (LiPF6) was quickly added thereto and stirred evenly. After passing the water and free acid tests, the desired electrolyte was obtained. The content of LiPF6 in the electrolyte was 15wt%.

[0122] (4) Diaphragm

[0123] The diaphragm includes a base film, a ceramic layer and a coating layer stacked in sequence, the ceramic layer is arranged on both sides of the base film, and the coating layer is arranged on the surface of the ceramic layer, wherein 5μm thick polyethylene (PE) is selected as the base film, and the total thickness of the ceramic layer and the coating layer is 4μm. The ceramic layer includes inorganic particles and a binder, wherein the inorganic particles are aluminum oxide particles, and the binder is polyacrylate. The coating layer includes polyvinylidene fluoride. The thickness B of the base film PE film is shown in Table 1, and the puncture force A, thickness N, deformation G and ionic conductivity J of the diaphragm are shown in Table 1.

[0124] (5) Lithium-ion battery

[0125] The positive electrode sheet, separator and negative electrode sheet are wound into a bare core in sequence, the bare cell is placed in an outer packaging foil, top and side sealed, baked to remove moisture, and then injected with electrolyte. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0126] Example 2-20

[0127] Example 2-20 provides a lithium-ion battery, which differs from Example 1 in that: the thickness B of the base film, the puncture force C of the positive electrode collector, the thickness D of the positive electrode collector, the puncture force E of the negative electrode collector, the thickness F of the negative electrode collector, L1, the deformation amount G generated by the puncture force of the diaphragm, the thickness H of the positive electrode sheet, the thickness I of the negative electrode sheet, the ionic conductivity J of the diaphragm, the surface resistance K of the first coating, the thickness M of the first coating and the thickness N of the diaphragm are different. The specific parameters are shown in Table 1.

[0128] Comparative Examples 1-3

[0129] Comparative Examples 1-3 provide a lithium-ion battery, which is different from Example 1 in that: the thickness B of the base film, the puncture force C of the positive electrode collector, the thickness D of the positive electrode collector, the puncture force E of the negative electrode collector, the thickness F of the negative electrode collector, L1, the deformation amount G generated by the puncture force of the diaphragm, the thickness H of the positive electrode sheet, the thickness I of the negative electrode sheet, the ionic conductivity J of the diaphragm, the surface resistance K of the first coating, the thickness M of the first coating and the thickness N of the diaphragm are different. The specific parameters are shown in Table 1.

[0130] Test Case

[0131] This test example provides the performance of the batteries of each embodiment and comparative example, as follows:

[0132] (1) Test method for puncture force of diaphragm and current collector: Cut the material to be tested into 10cm×10cm samples and fix them in the annular fixture at the bottom of the universal tensile machine. The upper fixture fixes the needle. When the test starts, the needle moves downward at a speed of 100mm / min. The maximum force applied to the needle during the penetration of the sample to be tested is the puncture force. The deformation G is calculated using G=L2-R. Calculated.

[0133] (2) Testing method of coating surface resistance: Use a bulk resistance meter to test the surface resistance.

[0134] Test method for ionic conductivity of diaphragm: Tested by ionic conductivity tester. Specifically include: cutting the diaphragm into circular samples with a diameter of 4cm, immersing it in electrolyte for 2h, and then placing 1 layer, 2 layers, 3 layers, 4 layers, and 5 layers of diaphragm in the middle of the upper and lower electrodes of the ionic conductivity tester 5 times respectively, the electrodes clamp the diaphragm, and measure the resistance values ​​R1, R2, R3, R4, and R5; using the number of diaphragm layers as the horizontal coordinate and the diaphragm resistance as the vertical coordinate, calculate the slope k of the curve, and substitute it into the following formula to calculate the ionic conductivity σ of the diaphragm. Among them, when the linear fit of the curve is greater than 0.99, calculate according to the following formula. When the linear fit is less than 0.99, it needs to be recalculated.

[0135] R=k×1

[0136]

[0137] Where R is the resistance value of one layer of the diaphragm, in Ω; k is the slope of the curve when the linear fit of the curve is greater than 0.99; d is the thickness of one layer of the diaphragm, in μm; S is the area of ​​the diaphragm, in cm 2 .

[0138] (3) Test method for low temperature cycle performance: The battery was placed in a low temperature test chamber (0±2)℃, and charged to 4.4V at a constant current density of 1.2C (cut-off current of 0.05C). After the battery was fully charged, it was left for 5 minutes, and then discharged at a constant current density of 0.5C (cut-off voltage of 3.0V). The discharge capacity was recorded as the initial capacity Q1. When the cycle reached 200 cycles, the last discharge capacity of the battery was recorded as Q2. The extreme capacity retention rate was calculated according to the following formula. The results are shown in Table 2.

[0139]

[0140] (4) Test method for needle puncture pass rate: fully charge the lithium-ion battery, then place it on the test bench of the needle puncture test equipment, and pierce the battery from the middle of the battery with a tungsten steel needle with a diameter of 3 mm and a needle tip length of 3.62 mm at a speed of 100 mm / s. The battery is considered to have passed the test if it does not catch fire or explode. The number of tests for each embodiment is 50. The needle puncture pass rate is calculated according to the following formula:

[0141] Needle puncture pass rate = number of passes / number of tests.

[0142] (5) Test method for heavy object impact pass rate: The battery is fully charged at an ambient temperature of (25±2)℃, the battery cell is placed on a plane, a steel column with a diameter of 15.8±0.2mm is placed in the center of the battery cell, and the longitudinal axis of the steel column is parallel to the plane. A weight of 9.1±0.1kg is allowed to fall freely from a height of 610±25mm onto the steel column above the center of the battery. After the test, the battery is recorded as passed if it does not catch fire, explode, or smoke. The number of tests for each embodiment is 50. The heavy object impact pass rate is calculated according to the following formula:

[0143] Heavy object impact pass rate = number of passes / number of tests.

[0144] Table 1 Parameters of each embodiment

[0145]

[0146]

[0147] Table 2 Test results of various embodiments

[0148] Example Capacity retention rate (%) Acupuncture pass rate Heavy object impact passing rate Example 1 97.90% 44 / 50pass 45 / 50pass Example 2 97.90% 48 / 50pass 47 / 50pass Example 3 97.90% 50 / 50pass 49 / 50pass Example 4 97.90% 48 / 50pass 48 / 50pass Example 5 97.90% 47 / 50pass 48 / 50pass Example 6 97.90% 48 / 50pass 49 / 50pass Example 7 97.90% 48 / 50pass 49 / 50pass Example 8 95.90% 48 / 50pass 48 / 50pass Example 9 97.90% 48 / 50pass 48 / 50pass Example 10 95.60% 46 / 50pass 46 / 50pass Embodiment 11 95.30% 46 / 50pass 47 / 50pass Example 12 97.90% 48 / 50pass 48 / 50pass Example 13 97.90% 49 / 50pass 48 / 50pass Embodiment 14 97.90% 47 / 50pass 46 / 50pass Embodiment 15 97.90% 49 / 50pass 48 / 50pass Example 16 97.80% 46 / 50pass 45 / 50pass Embodiment 17 97.90% 45 / 50pass 46 / 50pass Embodiment 18 97.90% 43 / 50pass 43 / 50pass Embodiment 19 94.20% 46 / 50pass 47 / 50pass Embodiment 20 97.90% 43 / 50pass 42 / 50pass Comparative Example 1 96.10% 37 / 50pass 37 / 50pass Comparative Example 2 95.80% 36 / 50pass 37 / 50pass Comparative Example 3 95.50% 30 / 50pass 29 / 50pass

[0149] It can be seen from the above results that the puncture force of the separator of the present invention, the thickness of the base film, the puncture force of the positive current collector, the thickness of the positive current collector, the puncture force of the negative current collector and the thickness of the negative current collector satisfy the relationship 1, and the puncture force A is 1N-8N, the thickness of the base film B is 3μm-16μm, the puncture force C of the positive current collector is 1N-10N, the thickness of the positive current collector D is 5μm-20μm, the puncture force E of the negative current collector is 1N-10N, and the thickness of the negative current collector F is 3μm-20μm. It can reduce the contact between the current collector and the active material during mechanical abuse, reduce the generation of short circuit points and heat generation, reduce the probability of thermal runaway, and improve the mechanical abuse test pass rate, such as the needle puncture pass rate and the heavy object impact pass rate are both high. When the above conditions are not met, problems such as low battery mechanical abuse test pass rate will occur.

[0150] In combination with Examples 18-20, the deformation G generated when the diaphragm puncture force is tested and the thickness H of the positive electrode sheet satisfies the relationship 2, or the deformation G generated when the diaphragm puncture force is tested and the thickness I of the negative electrode sheet satisfies the relationship 3, which can further improve the mechanical abuse test pass rate. The ionic conductivity J of the diaphragm and the surface resistance K of the first coating satisfy the relationship 4, which can further improve the safety performance and electrical performance of the battery. The thickness M of the first coating, the thickness N of the diaphragm and the thickness F of the negative electrode collector satisfy the relationship 6, which can further improve the battery mechanical abuse test pass rate.

[0151] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector; the separator comprises a base film; the puncture force A of the separator, the thickness B of the base film, the puncture force C of the positive electrode current collector, the thickness D of the positive electrode current collector, the puncture force E of the negative electrode current collector and the thickness F of the negative electrode current collector satisfy the relationship 1: Among them, A is 1N-8N; B is 3μm-16μm; C is 1N-10N; D is 5μm-20μm; E is 1N-10N; and F is 3μm-20μm.

2. The lithium-ion battery according to claim 1, characterized in that The deformation G generated when testing the diaphragm puncture force and the thickness H of the positive electrode sheet satisfy the relationship 2; G>H relation 2 Where G = L2-R, The L1 is the displacement of the needle when the septum is pierced during the puncture process, and the L1 is 1.5 mm-4.5 mm; the R is the distance from the point where the needle contacts the septum to the edge of the fixture when the needle just contacts the septum; The H is 50 μm-150 μm; Preferably, H is 60 μm-110 μm.

3. The lithium-ion battery according to claim 1, characterized in that The deformation G generated when testing the diaphragm puncture force and the thickness I of the negative electrode sheet satisfy the relationship 3: G>I relation 3 Where G = L2-R, The L1 is the displacement of the needle when the diaphragm is punctured during the puncture process, and the L1 is 1.5 mm-4.5 mm; the R is the distance from the point where the needle contacts the diaphragm to the edge of the fixture when the needle just contacts the diaphragm; the I is 50 μm-180 μm; Preferably, the I is 50 μm-100 μm.

4. The lithium-ion battery according to claim 1, characterized in that: A first coating is disposed on at least one surface of the positive electrode current collector; the first coating is disposed between the positive electrode current collector and the positive electrode active material layer, and the surface resistance of the first coating is 1 mΩ-1000 mΩ; Preferably, the surface resistance of the first coating layer is 1 mΩ-100 mΩ.

5. The lithium-ion battery according to claim 4, characterized in that: The first coating comprises a non-conductive organic polymer; Preferably, the non-conductive organic polymer is polymer particles.

6. The lithium-ion battery according to claim 4, characterized in that: The ionic conductivity J of the separator and the surface resistance K of the first coating satisfy the relationship 4: Wherein, the J is 0.1-5mS / cm; and the K is 1mΩ-100mΩ.

7. The lithium-ion battery according to claim 6, characterized in that: The ionic conductivity J of the separator and the surface resistance K of the first coating satisfy the relational expression 5:

8. The lithium-ion battery according to claim 4, characterized in that: The thickness M of the first coating layer, the thickness N of the separator, and the thickness F of the negative electrode current collector satisfy equation 6: Wherein, the M is 0.1 μm-5 μm; and the N is 3 μm-22 μm.

9. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The tensile strength of the diaphragm in the TD direction is 1200-7000kgf / cm 2 The tensile strength of the diaphragm in the MD direction is 1200-7000kgf / cm 2 and / or, The elongation at break of the separator in the TD direction is greater than 30%, and the elongation at break of the separator in the MD direction is greater than 30%; and / or, The puncture strength of the diaphragm is >120 gf.

10. The lithium ion battery according to any one of claims 1 to 9, characterized in that: The base film has a thickness of 3 μm-16 μm; and / or an air permeability of 50 s / 100 cc-250 s / 100 cc; and / or a porosity of 25%-50%; and / or a pore size distribution of 20 nm-90 nm.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery and method for producing nonaqueous electrolyte secondary battery

    CN112106245A

  • Isolating membrane and electrochemical device

    CN113991249A

  • Composite diaphragm and lithium ion battery

    CN116544612A

  • Electrochemical device, preparation method thereof and electric equipment

    CN118336078A

  • Lithium ion secondary battery

    CN1983679A